Isolamento, purificação e atividades biológicas de uma nova lectina de sementes de feijão da praia (Canavalia maritima) - Farias, Daniel Lima de (2013)
In many parts of the world leguminous plant is one of the most widely known plants previously reported. There are many different types of plants in the family leguminous used as food, in this case, the genus Canavalia comprises a group of some 48 species. The term lectin (derived from the latin word legere, meaning, among other things, to select) represent a heterogeneous group of proteins ranging from size, structure, molecular organization and constitution of interaction points as well as performing several biological activities such as anti-inflammatory, antifungal and antibiotic. Until now, the lectins of plants are one of the most studied, although some lectins in animals are well-specified. This research aim to isolate, purify and define biological activities of a new lectin present in the seeds of the Canavalia maritime. The results indicate the presence of a new lectin with a preference to agglutinate native erythrocytes of rabbit. These lectins were both purified in column chromatography of Sephadex G-50 and chitin, molecular exclusion in HPLC system, respectively. The purity and molecular weight (approximate) of the new lectin (from 50 to 55 kDa) was detected by SDS polyacrylamide gel electrophoresis. The new lectin did not cause hemolysis in human erythrocytes type A, O and AB, it reflects the interaction level of the sugars. According to sugar inhibition assays, the new lectin (content 71,5μg) indicates it is specific for arabinose, fructose, maltose, saccharose and xylose. On the other hand, the new lectin did not prevent the growth of tested bacterial strains, however, it is able to promote the proliferation these microorganisms. It also presented an anti-inflammatory activity as peritonitis induced by carrageenan in mice reducing the migration of neutrophils in the peritoneum of mice and permeability of the blood vessels. It also produced antifungal activity on the growth of the fungus C. neoformans, on its growth assay, evidenced by CIM determination, in this case, the results demonstrates no growth in the presence of the new lectin.